Research of routing protocol of wireless sensor network for coal mine goaf - XIA Xu; LI Wanghuai; LI Deng; CHEN Zhigang (Gong-kuang zidonghua, 2014)
In view of problem that current routing protocols of wireless sensor network based on energy balance are not suit to apply in coal mine goaf, the paper proposed an unequal clustering and energy-balanced routing protocol for coal mine goaf，namely UCEB-CMF protocol. Principle of the protocol is as follows: selection mechanism of candidate cluster-head is optimized to ensure sensor nodes with big residual energy to become candidate cluster-head. Calculating formula of unequal competition radius and competition method of the candidate cluster-head are improved, which adds consideration for distance from cluster-head node to Sink node on basis of consideration of residual energy, so as to realize energy balance. In view of characteristics of being easy to die of sensor nodes in coal mine goaf, a routing algorithm with multipath was proposed, so as to realize persistence of data transmission. The simulation result shows that the protocol can balance energy of sensor nodes effectively and prolong survival time of wireless sensor network, which is suite to apply in coal mine goaf.